IMPLEMENTATION OF ACCOUNTABILITY AND TRANSPARENCY BASED ON FACILITIES AND INFRASTRUCTURE MANAGEMENT IN SUPPORTING THE GOVERNANCE OF THE S1 ISLAMIC EDUCATION MANAGEMENT STUDY PROGRAM - Setiawan, Dodi; Rismawan, Heri; Febriani, Syifa (Jurnal Multidisipliner Bharasa, 2026)
This study aims to analyze the implementation of accountability and transparency-based facilities and infrastructure management in supporting the governance of the S1 Islamic Education Management (MPI) Study Program. The management of facilities and infrastructure is one of the strategic components in the higher education system that plays a significant role in improving academic quality, learning effectiveness, and institutional credibility. In the context of higher education governance which increasingly demands the principles of good governance, accountability and transparency are important indicators in the process of planning, procurement, utilization, maintenance, and evaluation of facilities and infrastructure. This study uses a qualitative approach with a case study design in the MPI S1 Study Program at one of the Islamic religious universities. Data were obtained through in-depth interviews, participatory observations, and documentation studies that were analyzed using data reduction techniques, data presentation, and systematic conclusion drawn. The results of the study show that the implementation of accountability and transparency-based facility and infrastructure management is reflected in the preparation of needs-based planning, open reporting of budget use, stakeholder involvement in decision-making, and the existence of a sustainable internal monitoring mechanism. However, there are still several obstacles such as limited human resources, non-optimal management information systems, and low student participation in the evaluation process. This study concludes that strengthening the accountability and transparency system in the management of facilities and infrastructure contributes positively to improving the governance of study programs, especially in the aspects of effectiveness, efficiency, and public trust.